2018
DOI: 10.1016/j.bpj.2018.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Energetics of Loop Extensions in a Family of Tandem-Repeat Proteins

Abstract: Consensus-designed tetratricopeptide repeat proteins are highly stable, modular proteins that are strikingly amenable to rational engineering. They therefore have tremendous potential as building blocks for biomaterials and biomedicine. Here, we explore the possibility of extending the loops between repeats to enable further diversification, and we investigate how this modification affects stability and folding cooperativity. We find that extending a single loop by up to 25 residues does not disrupt the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…These studies will allow us to understand the relationship between the length/sequence composition of the grafted peptide and its binding affinity within the context of the CTPR scaffold. In terms of the maximum peptide length, we have found that we can successfully graft binding peptides of up to 15 residues onto the inter‐repeat loop, and we have also shown that the loop can be extended by up to 40 residues without disrupting the CTPR structure (; unpublished results).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…These studies will allow us to understand the relationship between the length/sequence composition of the grafted peptide and its binding affinity within the context of the CTPR scaffold. In terms of the maximum peptide length, we have found that we can successfully graft binding peptides of up to 15 residues onto the inter‐repeat loop, and we have also shown that the loop can be extended by up to 40 residues without disrupting the CTPR structure (; unpublished results).…”
Section: Resultsmentioning
confidence: 79%
“…The high thermodynamic stabilities of CTPRs combined with their modular nature means that even gross modifications are still likely to produce proteins with high stabilities, and indeed we recently showed that CTPR proteins can tolerate extension of the inter‐repeat loop by up to 25 residues . Here, we take advantage of this malleability to describe a new strategy for engineering high‐affinity binding functions into CTPR proteins by grafting functional peptides into the inter‐repeat loop.…”
Section: Introductionmentioning
confidence: 99%
“…This may not be the case for other proteins and has to be verified on a case-by-case basis. Moreover, the application of the ybbR-tag has limitations for the introduction of internal attachments sites, particularly in a repeat protein context where we have found that simple unstructured loops destabilize the array 23 . We expect that the introduction of a short α-helix would have an even greater effect, even if it is accompanied by unstructured spacers either side.…”
Section: Resultsmentioning
confidence: 95%
“…This is referred to as a homopolymer Ising model 10,25 . The stabilities of non-identical repeat proteins can also be described using an Ising model, but a more complex description is required, which is referred to as the heteropolymer model 25–29 .…”
Section: Introductionmentioning
confidence: 99%